2015
DOI: 10.3354/meps11127
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass deterrence to mesograzer herbivory: evidence from mesocosm experiments and feeding preference trials

Abstract: Running head: Effects of mesograzer feeding on seagrass phenolics This is a pre-print version of the manuscript. It is not the final copy-edited version, but all figures are identical to those in the final, published article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…While we hypothesized that changes in choice patterns and feeding rates were the result of C:N ratios, it is also possible that an undocumented and unquantified covarying variable influenced this trend. For example, C:N may be correlated with phenolics or other chemical defenses that would alter feeding patterns [68]. Moreover, we know little about the levels of ecological significance in these ratios and a better understanding of food web dynamics may be attained by determining variability in C:N ratios and the ensuing food web consequences.…”
Section: Discussionmentioning
confidence: 99%
“…While we hypothesized that changes in choice patterns and feeding rates were the result of C:N ratios, it is also possible that an undocumented and unquantified covarying variable influenced this trend. For example, C:N may be correlated with phenolics or other chemical defenses that would alter feeding patterns [68]. Moreover, we know little about the levels of ecological significance in these ratios and a better understanding of food web dynamics may be attained by determining variability in C:N ratios and the ensuing food web consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, grazer-damage has been reported to induce a different plant response than physical damage alone [ 33 , 34 , 35 ]. Despite these indications, in a recent study, Steele and Valentine [ 36 ] found no induced change in the palatability of two tropical seagrass species to the isopod Paracerceis caudata after a 15-day induction experiment. Therefore, in order to understand the general significance of inducible defences in seagrasses we first need to provide a solid assessment of whether mesograzers are able to induce defences that deter consumption and how this may vary among different seagrass and mesograzer species.…”
Section: Introductionmentioning
confidence: 98%
“…Seagrasses exposed to herbivory may decline or die-off, exhibit tolerance through compensatory or super-compensatory growth, or display resistance by altering their physiology or chemistry through methods such as nutrient or carbohydrate re-routing or by producing secondary metabolites (Cebrian et al 1998, Ricklefs and Miller 1999, Vergés et al 2008, Burnell et al 2013a, Steele and Valentine 2015. The tolerance of primary producers to different kinds of herbivory differs by species-though it can also be induced in response to herbivory (e.g., Burnell et al 2013a, Sanmarti et al 2014-and this differential tolerance can have implications for seagrass community composition.…”
Section: The Role Of Seagrass In Mediating the Strength Of Top-down Pmentioning
confidence: 99%
“…Similarly, in Watamu National Marine Park, Kenya, feeding preferences of the teleost herbivore Calotomus carolinus are inversely correlated to the carbon fiber content of primary producer species (Mariani and Alcoverro 1999, Table 1). The relationship between nutrient ratios, plant defenses, and herbivore feeding preference is further obscured by the fact that plant characteristics can fluctuate across space, time, species, and individual (e.g., Fourqurean et al 2005, Hays 2005, Tomas et al 2011, Steele and Valentine 2015. This complicates drawing patterns because multiple chemical variables can change concurrently, making attribution of herbivory to a single compound or group of compounds difficult.…”
Section: The Role Of Seagrass In Mediating the Strength Of Top-down Pmentioning
confidence: 99%
See 1 more Smart Citation